Barriers and enablers in integrating cognitive apprenticeship methods in a Web-based educational technology course for K–12 (primary and secondary) teacher education - Michele D. Dickey (Association for Learning Technology, 2007)
The purpose of this study is to investigate the integration of a cognitive apprenticeship model into an educational technology Web-based course for pre-service primary through secondary teacher education. Specifically, this study presents an overview of methods, tools and media used to foster the integration of a cognitive apprenticeship model, and presents the types of barriers and enablers encountered when attempting to participate in a computer-mediated cognitive apprenticeship. The methodological framework for this investigation is a qualitative case study of an educational technology course for pre-service primary through secondary teacher education. The findings of this study reveal that various tools, methods and media were used to varying degrees of success to foster cognitive apprenticeship methods in a Web-based learning environment. The goal of this study was to better understand the pragmatics, suitability, affordances and constraints of integrating cognitive apprenticeship methods in a Web-based distance education course for teacher education.